2021
DOI: 10.1002/clt2.12047
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL‐17 in atopy—A systematic review

Abstract: Purpose of Review: Atopy is defined as the genetic predisposition to react with type I allergic diseases such as food-, skin-, and respiratory allergies. Distinct molecular mechanisms have been described, including the known Th2 driven immune response. IL-17A (IL-17) is mainly produced by Th17 cells and belongs to the IL-17 family of cytokines, IL-17A to F. While IL-17 plays a major role in inflammatory and autoimmune disorders, more data was published in recent years elucidating the role of IL-17 in allergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…The asthma course is influenced by T cells subset and cytokines, such as NKT and Tregs. In contrast to Treg that has a protective role in asthma, Th17-associated cytokines can increase the severity [70][71][72].…”
Section: Asthmamentioning
confidence: 96%
“…The asthma course is influenced by T cells subset and cytokines, such as NKT and Tregs. In contrast to Treg that has a protective role in asthma, Th17-associated cytokines can increase the severity [70][71][72].…”
Section: Asthmamentioning
confidence: 96%
“…99 In addition, a high level of IL-17 produced by Th17 cells has been reported to contribute to AD pathogenesis since IL-17 stimulates keratinocytes to produce IL-6 and IL-8 increasing T cell migration to the skin. 100 Thus, most of the currently used therapies (corticosteroids, calcineurin inhibitors, leukotriene receptor antagonists and antihistamine) to manage AD patients aim to govern improper the Th1/Th2 imbalance and to alleviate symptoms. 101 Recently, the immunomodulatory effect of ADSC-based therapy has been proposed for AD treatment.…”
Section: Acnementioning
confidence: 99%
“…However, to date, most studies on the role of IL-17A in the pathogenesis of allergic diseases have been carried out using animal models, so it is difficult to apply the obtained conclusions to humans. In the course of AD, an elevation of the transcript of another member of IL-17 family (IL-17E) was found [99]. Yesilova et al indicated high levels of TNF-alpha in children with atopic lesions [100].…”
Section: Atopic Dermatitis (Ad)mentioning
confidence: 99%